2021
DOI: 10.3389/fmed.2021.638194
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Coagulation Function of Patients With COVID-19 Is Significantly Related to Hypocalcemia and Severe Inflammation

Abstract: This study aimed to detect, analyze, and correlate the clinical characteristics, blood coagulation functions, blood calcium levels, and inflammatory factors in patients with mild and severe COVID-19 infections. The enrolled COVID-19 infected patients were from Wuhan Jin Yin-tan Hospital (17 cases, Wuhan, China), Suzhou Infectious Disease Hospital (87 cases, Suzhou, China), and Xuzhou Infectious Disease Hospital (14 cases, Xuzhou, China). After admission, basic information was collected; X-ray and chest CT imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
3
16
1
Order By: Relevance
“…In our study, calcium serum levels were negatively correlated with three measured clinical outcomes: the length of hospitalization (days), the severity of the course of COVID-19 (1-4), and oxygen flow (l/min). These findings were consistent with previously published reports which have showed that low serum calcium levels are associated with disease severity and a poor prognosis for patients with COVID-19 [ 50 - 53 ]. In a study by Zhang et al low serum calcium levels were the most predictive feature of COVID-19 diagnosis of all models tested [ 54 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, calcium serum levels were negatively correlated with three measured clinical outcomes: the length of hospitalization (days), the severity of the course of COVID-19 (1-4), and oxygen flow (l/min). These findings were consistent with previously published reports which have showed that low serum calcium levels are associated with disease severity and a poor prognosis for patients with COVID-19 [ 50 - 53 ]. In a study by Zhang et al low serum calcium levels were the most predictive feature of COVID-19 diagnosis of all models tested [ 54 ].…”
Section: Discussionsupporting
confidence: 94%
“…According to the previous studies, levels of the disease progression indicators CRP, PCT, IL-6, and D-dimer are found to be significantly higher in COVID-19 patients with hypocalcemia. When this is coupled with calcium serum levels which are negatively correlated with these indicators, it means that these patients may have www.bjbms.org a greater inflammatory response [50,51,53]. Secondly, the occurrence of hypocalcemia may be associated with calcium inflow due to hypoxemic tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the present paper have been collected in a sample of 2473 patients admitted for COVID-19 in a general hospital. In agreement with previous reports [8][9][10][11][12], our data show that most of the registered comorbidities and laboratory parameters were related to the poor outcome of the disease and to in-hospital mor- This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.…”
Section: Discussionsupporting
confidence: 92%
“…1 ). These mechanisms include calcium-dependent viral mechanisms of action determining intra and extra-cellular cation dysmetabolism [ 22 24 ], tissues calcium deposits detected at autoptic evaluation [ 25 ], acute muscle calcium precipitation [ 26 ], calcium role in coagulation and prothrombotic status [ 27 , 28 ], acute malnutrition during critical illness [ 29 ], high levels of unbound and unsaturated fatty acids in inflammatory responses [ 30 ] and high prevalence of hypovitaminosis D with an impaired compensatory PTH response [ 31 ]. Furthermore, severe hypocalcemia, although not frequently found in COVID-19 [ 3 , 13 ], may compromise outcome per se due to its additional negative cardiovascular and neurological impact [ 3 , 13 ].…”
Section: Hypocalcemiamentioning
confidence: 99%